Government innovation support for green development efficiency in China: A regional analysis of key factors based on the dynamic GMM model - Khattak, Shoukat Iqbal; Khan, Muhammad Kamran; Sun, Taipeng; Khan, Uzma; Wang, Xiaoman; Niu, Yating (Frontiers in Environmental Science, 2022)
Local government innovation support is an exogenous pulling force for high-quality economic development. Accurately identifying the mechanism by which local government innovation support affects green development has great theoretical and practical significance for building a long-term framework for driving green development. Based on the panel data of 30 provinces and cities in China from 2010 to 2019, this paper uses the Super-SBM model to measure the provincial-level green development efficiency. Also, the article examines the impact of local government innovation on green development efficiency using the dynamic panel GMM model. The results show that local government innovation support has a promoting effect on green development efficiency, and the green development efficiency in the first lag period has an improving effect on the green development efficiency in the current period. However, due to the influence of the decline in innovation support and environmental regulations, the lag period of the second period is limited. The promotion effect of green development efficiency on the current period has slowed down significantly. Based on the above research findings, at this stage, China should further increase the government's innovation support to promote the efficiency of regional green development and achieve high-quality economic development.